De tierra sin pan a valle de la muerte: Las Hurdes de Buñuel en clave tematológica (Altre Modernità, 2015)
The premiere in 1933 of the famous audiovisual documentary by Spanish director Luis Buñuel, today unanimously applauded as one of the most accomplished in the history of cinema, was a great event and, moreover, a scandal in Europe. Prohibited both by the authorities of the Spanish Republic and those of the French, the film intended to raise its public about the problems associated with extreme scarcity and hunger, turning the region of Las Hurdes in synecdoche for the whole Spain. This article aims to use the tools of thematology to test the force lines of a documentary built on the topics of the lack of bread and food, the spread of the disease and the coexistence with death.